EFEKTIFITAS KOMITE AUDIT DAN TERJADINYA FRAUD - , CHRISTINE NOVITA DEWI, Prof. Dr. Gudono, MBA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Purpose â The purpose of this study is to examine empirically influence the audit committee effectiveness to the fraud occurrence within state-owned enterprises/BUMN (BUMN). Design/methodology/approach â Using Structural Equation Modeling which performed with Partial Lease Square (PLS) software, research has been done upon 31 of 141 BUMNâs which actively operated in Indonesia for the period of 2007 â 2010 or about 22 percent from existing BUMN. Samples were selected with purposive sampling method. Findings â The findings indicates that audit committee effectiveness is negatively associated with the fraud indication within BUMN. The more effective audit committee which is described by expertise, size and activeness audit committee in carrying out the role and duties, the less indication of fraud exists. In this research, expertise is represented by education level, origin university, and educational background composition of audit committee. At the first stage alogaritma testing indicates that only composition of educational background has loading score more than 0.5, so educational level and university have to be taken out from the research model. Bootstrapping test results that size of audit committee has highest loading score was 0.7910 while activeness and educational background composition has 0.7287 and 0.6917 respectively. It was intepretated that size of audit committee was on the first rank to achive audit committee effectiveness, followed by activeness and educational background. Practical Implication â Research on audit committee effectiveness and fraud occurrence has been conducted only in BUMN, while in private company hasnât yet. It makes there is wide open opportunity to conduct similar research in private sector. Findings in this study is strengthening argument that the policy maker should concern and take a significant action on mainstreaming audit committee in order to reduce fraud occurrence. Originality/value â This research is the first empirical research conducted in Indonesia, which the result is expected being an important input on the implementation of good corporate governance and audit literature.